Methods in maritime education for analysis of factors influencing shipping and marine environment in the western part of the Black Sea - Poenaru, Valentina; Novac, Valerian; Bazaitu, Razvan (Technium Social Sciences Journal, 2020)
The marine environment is a complex environment that includes both the water and the area of ??air moving through the vessel. Depending on its mode of expression, its status parameter value, it produces direct effects, favorable and unfavorable, on navigation. Modern Meteorology and Oceanography operating methods and procedures for obtaining data for education, necessary for determining regularities that lead to phenomena and processes which occur in interdependent layers, in the marine environment and the atmosphere above the ocean (waves, storms, rain, currents, the impact on the safety of life, activities and maritime navigation challenges - in terms of visibility, stability, and immovability of the ship